2012
DOI: 10.1049/iet-sen.2011.0125
|View full text |Cite
|
Sign up to set email alerts
|

Systematic literature review: teaching novices programming using robots

Abstract: Teaching programming to novices is a difficult task due to the complex nature of the subject, the negative stereotypes are associated with programming and because introductory programming courses often fail to encourage student understanding. This study investigates the effectiveness of using robots as tools in the teaching of introductory programming and to determine whether such technology can help to overcome the current barriers for learners in this context. The systematic literature review (SLR) methodolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(27 citation statements)
references
References 15 publications
2
23
0
1
Order By: Relevance
“…Foram localizadas quatro publicações que tratam, não especificamente do desenvolvimento do PC por meio da robótica, mas da robótica como ferramenta para ensino de programação [Major et al 2012], robótica nas escolas (educação) [Benitti 2012, Neto et al 2015 e movimento maker na educação [Papavlasopoulou et al 2017]. Considerando o fato destas revisões não tratarem, especificamente, sobre PC, prosseguiu-se com a criação de uma nova RSL para conhecer e sintetizar os resultados dos estudos sobre o assunto nosúltimos cinco anos (2012 a 2016).…”
Section: Metodologiaunclassified
“…Foram localizadas quatro publicações que tratam, não especificamente do desenvolvimento do PC por meio da robótica, mas da robótica como ferramenta para ensino de programação [Major et al 2012], robótica nas escolas (educação) [Benitti 2012, Neto et al 2015 e movimento maker na educação [Papavlasopoulou et al 2017]. Considerando o fato destas revisões não tratarem, especificamente, sobre PC, prosseguiu-se com a criação de uma nova RSL para conhecer e sintetizar os resultados dos estudos sobre o assunto nosúltimos cinco anos (2012 a 2016).…”
Section: Metodologiaunclassified
“…The Kilobot [16] and GRITSbot [17] are very small, affordable robots that have been developed for swarm robotic experiments. The Pololu 3pi [18] is a small hobby platform with very limited sensing. The LEGO Mindstorms [19] and iRobot Create 2 [18] are designed for education and can be given augmented capabilities through accessories and expansion packs.…”
Section: Existing Platformsmentioning
confidence: 99%
“…The Pololu 3pi [18] is a small hobby platform with very limited sensing. The LEGO Mindstorms [19] and iRobot Create 2 [18] are designed for education and can be given augmented capabilities through accessories and expansion packs. The LEGO Mindstorms kit has a specific set of sensors and chassis components, allowing up to four sensors and four motors to be driven at once.…”
Section: Existing Platformsmentioning
confidence: 99%
“…The main goal of using robotics on education is learning STEM concepts through hands-on learning activities [4], and in this way encouraging team work within a multi-disciplinary environment. In the past few years, robotics on education has become an interesting research topic; for instance, [1] and [5] reported 197 different scientific works on this area over the past 10 years. These studies showed that robotics on education is an important tool to improve the learning process, not only at secondary level, but in Universities as well.…”
Section: Introductionmentioning
confidence: 99%